Decompressive Craniectomy after Severe Traumatic Brain Injury in Children: Complications and Outcome - Pechmann, Astrid; Anastasopoulos, Constantin; Korinthenberg, Rudolf; van Velthoven-Wurster, Vera; Kirschner, Janbernd (Neuropediatrics, 2015)
Decompressive craniectomy (DC) is a controversially discussed neurosurgical procedure to reduce elevated intracranial pressure after severe traumatic brain injury (TBI). In contrast to adults, several studies could show a benefit for the pediatric population, but still DC is considered as an emergency procedure only. The aim of our study was to identify secondary complications and long-term sequelae of the procedure. All children presenting to the University Medical Center Freiburg between 2005 and 2013 who underwent DC after severe TBI were retrospectively reviewed with respect to complications and outcome. Twelve children were included with a mean Glasgow Coma Scale of 4.5 ± 1.7. The most frequent complications after TBI and DC were formation of hygroma (83%), aseptic bone resorption of the reimplanted bone flap (50%), posttraumatic hydrocephalus (42%), secondary infection or dysfunction of ventriculoperitoneal shunt (25%) or cranioplasty (33%), and epilepsy (33%). Because of these complications, 75% of patients required further surgery in addition to cranioplasty with up to eight interventions. At follow-up, mean Glasgow Outcome Scale was 3.3 ± 1.2. Within our patient population, we demonstrated high incidence of complications after DC, leading to further surgical procedures and longer hospitalization. These potential complications have to be considered in any decision about DC as an emergency procedure.
Keywords: traumatic brain injury; decompressive craniectomy; children; complications; outcome